PERBANDINGAN SPIRITUAL EMOTIONAL FREEDOM TEHNIQUE DAN PROGRESSIVE MUSCLE RELAXATION TERHADAP KUALITAS TIDUR PENDERITA HIPERTENSI DI CILACAP SELATAN - Kasron Kasron (Poltekkes Kemenkes Pangkalpinang, 2018)
Patients with hypertension patients can have sleep disorders such as dizziness or headache,. This study aimed to evaluate the effect of spiritual emotional freedom tehnique (SEFT) and progressive muscle relaxation (PMR) on sleep quality in patients with hypertension in South Cilacap City. The research used quasi-experiment with two group pre-post test group. Respondents were patients with hypertension, with the criteria forthose who were active in health care programme, able to perform independent activities, consume of anti-hypertensive drugs, have done SEFT and PMR regularly for 7 days. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality twice, before and 7 days after interventions SEFT. Statistic analysis used Mann-Whitney test. 32 respondents included in the criteria. The quality of sleep before treatment SEFT was 43.8% poor, 56.3% very bad. After treatment SEFT was 25% rather good, 75% less good. The quality of sleep before treatment PMR was 43.8% poor, 56.3% very bad. After treatment PMR was 18.8% rather good, 81.3% less good. The analysis shown the sleep quality was difference between SEFT and PMR after intervention with p-value 0.002. The study shows there is difference between SEFT and PMR after intervention in hypertensive patients in South Cilacap